Low-density lipoprotein cholesterol and risk of COPD: Copenhagen General Population Study. Issue 2 (6th March 2023) - Freyberg, Josefine; Landt, Eskild M.; Afzal, Shoaib; Nordestgaard, Børge G.; Dahl, Morten
Background: Randomised controlled trials found that low-density lipoprotein (LDL) cholesterol-lowering statins increase lung function and possibly decrease rate of exacerbations in individuals with COPD. However, it is unknown whether high levels of LDL cholesterol are associated with increased susceptibility to COPD. Methods: We tested the hypothesis that high LDL cholesterol is associated with increased risk of COPD, severe COPD exacerbation and COPD-specific mortality. We examined 107 301 adults from the Copenhagen General Population Study. COPD outcomes were ascertained at baseline and prospectively through nationwide registries. Results: In cross-sectional analysis, low LDL cholesterol was associated with increased risk of COPD (odds ratio for 1st versus 4th quartile: 1.07 (95% CI 1.01–1.14)). Prospectively, low LDL cholesterol was associated with increased risk of COPD exacerbations with hazard ratios of 1.43 (1.21–1.70) for 1st versus 4th quartile, 1.21 (1.03–1.43) for 2nd versus 4th quartile, and 1.01 (0.85–1.20) for 3rd versus 4th quartile of LDL cholesterol (p-value for trend=6×10 −6 ). Finally, low LDL cholesterol was likewise associated with increased risk of COPD-specific mortality (log-rank test: p=0.0009). Sensitivity analyses with death as competing risk provided similar results. Conclusion: Low LDL cholesterol was associated with increased risks of severe COPD exacerbation and COPD-specific mortality in the Danish general population. As this is opposite of that observed in randomised controlled trials with statins, our findings might be a result of reverse causation indicating that individuals with severe phenotypes of COPD have lower plasma levels of LDL cholesterol due to wasting. Low plasma levels of LDL cholesterol are associated with increased risk of COPD, COPD exacerbation and COPD-specific mortality in adults in the general population https://bit.ly/3Ow16BC